Analisa Kemampuan Mengontrol Marah ditinjau dari Penerapan REBT (Rational Emotive Behaviour Theraphy) pada Klien Skizofrenia di UPT Bina Laras Kras Kediri - Wardani, Lingga Kusuma; Sari, Dhita Kurnia (STRADA : Jurnal Ilmiah Kesehatan, 2018)
One of schizophrenia symptoms is tantrum; to hurt people and environment, it is done to express resentment or anger which is not constructive. Anger is an aggravation which emerges as a response to anxiety or unfulfilled need and perceived as a threat. This research aims to analyze the relation between REBT (Rational Emotive Behaviour Therapy) and the ability to control anger to schizophrenics in UPT Bina Laras Kras Kediri. Research design uses observational analytic with crossectional approach. The population is all schizophrenics in UPT Bina Laras Kras Kediri, the sampling technique used is purposive sampling by getting 13 respondents, the data collection used are REBT questionnaire and observation sheet of the ability to control anger. Data analysis uses Chi-Square with p value 0,001 < ɑ 0,05 means there is a relation between REBT application and the ability to control anger to schizophrenia patients in UPT Bina Laras Kras Kediri.